96.3k views
1 vote
I need help don’t understand

I need help don’t understand-example-1
User Henry Tao
by
5.6k points

2 Answers

0 votes
If f(x)=x+1 and then x became 2, you would have the function f(x)=3. So basically for that function you would be going up three over 1. That function is already g(x)=4x. If X became 2, you would have g(x)=8x. The rate of up 8 and then over one. Because of that, g(x) would be higher
User Chris Felstead
by
5.2k points
1 vote

okay first off: we both use the same virtual school and i just thought that was cool lol

the equation for g(x) is g(x)=4x-5 so when you substitute in x it becomes

g(x)= 4(2) -5 or g(x)= 8-5 which equals g(x)=3

when you substitute in x, f(x) becomes

f(x)= 2 + 1 which equals f(x)=3

therefore when x=2, both functions are equal :)

hope this helps!!

User Gary Chang
by
5.6k points